2015
DOI: 10.4238/2015.december.29.26
|View full text |Cite
|
Sign up to set email alerts
|

A wavelet-based feature vector model for DNA clustering

Abstract: ABSTRACT. DNA data are important in the bioinformatic domain. To extract useful information from the enormous collection of DNA sequences, DNA clustering is often adopted to efficiently deal with DNA data. The alignmentfree method is a very popular way of creating feature vectors from DNA sequences, which are then used to compare DNA similarities. This paper proposes a wavelet-based feature vector (WFV) model, which is also an alignment-free method. From the perspective of signal processing, a DNA sequence is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…The clustering analysis is often adopted to deal with DNA sequences efficiently. A wavelet-based feature vector model was proposed by Bao and Yuan (2015) for clustering of DNA sequences.…”
Section: Introductionmentioning
confidence: 99%
“…The clustering analysis is often adopted to deal with DNA sequences efficiently. A wavelet-based feature vector model was proposed by Bao and Yuan (2015) for clustering of DNA sequences.…”
Section: Introductionmentioning
confidence: 99%
“…The clustering analysis is often assumed to deal with DNA sequences proficiently. A wavelet-based element vector model was anticipated for grouping of DNA sequences [10].…”
Section: Wavelet Analysismentioning
confidence: 99%
“…The clustering analysis is often adopted to deal with DNA sequences efficiently. A wavelet-based feature vector model was proposed by Bao and Yuan (2015) for clustering of DNA sequences. Saini and Dewan (2016) based on the calculation of the energy of wavelet decomposition coefficients of complete genomic sequences showed that the genomic sequences of MTB could be grouped only into two groups.…”
Section: Introductionmentioning
confidence: 99%